2011
DOI: 10.1063/1.3575497
|View full text |Cite
|
Sign up to set email alerts
|

A study of electron scattering from benzene: Excitation of the 1B1u, 3E2g, and 1E1u electronic states

Abstract: We report results from measurements for differential and integral cross sections of the unresolved 1B1u and 3E2g electronic states and the 1E1u electronic state in benzene. The energy range of this work was 10–200 eV, while the angular range of the differential cross sections was ∼3°–130°. To the best of our knowledge there are no other corresponding theoretical or experimental data against which we can compare the present results. A generalized oscillator strength analysis was applied to our 100 and 200 eV di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 60 publications
9
36
2
Order By: Relevance
“…6 the present data agree very well with the pyrimidine data of Jones et al 12 which is also shown in the figure, except that the present data are slightly larger in the range V. The benzene and pyrimidine data are nearly identical as indicated by the benzene data of Kato et al, 49 also given in Fig. 6.…”
Section: A Dependence On Electron Energysupporting
confidence: 82%
See 2 more Smart Citations
“…6 the present data agree very well with the pyrimidine data of Jones et al 12 which is also shown in the figure, except that the present data are slightly larger in the range V. The benzene and pyrimidine data are nearly identical as indicated by the benzene data of Kato et al, 49 also given in Fig. 6.…”
Section: A Dependence On Electron Energysupporting
confidence: 82%
“…7 and 8. The present pyrimidine data are, however, in very good agreement with the benzene data of Kato et al, 49 indicated by triangles in Figs. 7 and 8, especially in the range IV.…”
Section: A Dependence On Electron Energysupporting
confidence: 78%
See 1 more Smart Citation
“…Note that similar estimates for the forward angle extrapolation of inelastic transitions have been successful for many other targets. [40][41][42] In the present work, the derived GOS-dipole forward angle extrapolation, plus or minus 50% (commensurate to the experimental uncertainty on the DCS data), is used as the range of forward angle DCS values in order to calculate realistic uncertainties for the derived ICS. The ICSs derived using the GOS-dipole extrapolation are also presented in Table III.…”
Section: Experimental Methods and Analysis Techniquementioning
confidence: 99%
“…Nonetheless, we caution that the Born approximation is not a very sophisticated approach and that as a result of this scaling procedures are often employed in conjunction with its use. 33,34 …”
Section: A Low Energies and Low Fields (0 E/n 0 35 Td) -The Need Formentioning
confidence: 99%